PERPUSTAKAAN UMUM DENGAN PENDEKATAN ARSITEKTUR HIJAU DI KOTA MAGELANG - Ridhati Ummi Waskitarini; Edo Pramono Singgih; Tri Yuni Iswati (Universitas Sebelas Maret Surakarta, 2015)
Designing Public Library Magelang motivated by the low public interest in reading, support the efforts of the government of Magelang in raising interest in reading, as well as the need for educational facilities such as adequate library in Magelang, so the purpose of this architectural planning is to get the design of the educational facilities building that can be means for information needs, education needs and recreation needs for the Magelang society which is the building is able to maintain harmony with the surrounding natural environment. The issue of the design are: how to build a public library of Magelang, that could accommodate the needs of the community reading Magelang. The appearance of this Public Library building based on the principles of Green Architecture. The approach used in determining the design is by using the principles of green architecture based on the standard GREENSHIP Indonesia, which is about the Appropriate Site Development, Energy Efficiency and Conservation, Water Conservation, Material Resources and Cycle, Indoor Health and Comfort, and Building Environment and Management. The result obtained is the design of a municipal public library building with green architecture in accordance with the standards of Indonesian GREENSHIP design consideration so that the existence of the building is expected to maintain harmony with the surrounding nature. Keywords: Architecture, Library, Public Library, Green Architecture